Пьезоэлектрический волноводный датчик для измерения импульсного давления в замкнутых объемах жидкости при высоковольтном электрическом разряде - Жекул, Василий Григорьевич; Смирнов, Алексей Петрович; Тафтай, Эдуард Иванович; Хвощан, Олег Вильямович; Швец, Иван Сафронович (НТУ "ХПИ", 2017)
На основании проведенного анализа рынка приборов, измеряющих импульсное давление, выбрана конструкция и схемное решение помехоустойчивого волноводного датчика давления, обеспечивающего стабильность и достоверность показаний на близком расстоянии от канала высоковольтного электрического разряда в замкнутом объеме жидкости. Разработан волноводный датчик импульсного давления ДТХ-1 с измерительным шлейфом, позволяющий исследовать спектральные характеристики волн давления в закрытых объемах жидкости при гидростатическом давлении до 20 МПа и температуре до 80 °С. Датчик может быть применен для изучения волн давления с максимальным амплитудным значением до 150 МПа и длительностью до 80 мкс. Согласно результатам тарировки с использованием вторичного эталона, чувствительность датчика ДТХ-1 с измерительным трактом - 0,0346 В/МПа.

Investigations of the characteristics of pressure waves presuppose the registration of the total profile of the pressure wave at a given point in space. For these purposes, various types of "pressure to the electrical signal" transmitters (sensors) are used. Most of the common sensors are unsuitable for measuring the pulse pressure in a closed water volume at high hydrostatic pressures, in particularto study the effect of a powerful high-voltage pulse discharge on increasing the inflow of minerals and drinking water in wells. The purpose of the work was to develop antijamming piezoelectric waveguide sensor for measuring pulse pressure at a close distance from a high-voltage discharge channel in a closed volume of a liquid. We have applied the calibration method as used as a secondary standard, the theory of electrical circuits. We have selected the design and the circuit solution of the waveguide pressure sensor. We have developed a waveguide pulse-pressure sensor DTX-1 with a measuring loop. This sensor makes it possible to study the spectral characteristics of pressure waves of high-voltage pulse discharge in closed volumes of liquid at a hydrostatic pressure of up to 20 MPa and a temperature of up to 80 °C. The sensor can be used to study pressure waves with a maximum amplitude value of up to 150 MPa and duration of up to 80 µs. According to the results of the calibration, the sensitivity of the developed sensor DTX-1 with a measuring loop is 0.0346 V/MPa. We have further developed the theory of designingthe waveguide piezoelectric pulse pressure sensors for measuring the pulse pressure at a close distance from a high-voltage discharge channel in a closed fluid volume by controlling the attenuation of the amplitude of the pressure signal. We have developed, created, calibrated, used in scientific research waveguide pressure pulse sensors DTX-1. We propose sensors DTX-1 for sale in Ukraine and abroad. Sensors DTX-1 can be used to study pressure waves with a maximum amplitude value of up to 150 MPa in closed fluid volumes at a hydrostatic pressure of up to 20 MPa and a temperature of up to 80 °C.
Piezoelectric waveguide sensor for measuring pulse pressure in closed liquid volumes at high voltage electric discharge
Keywords: гидростатические давления; источник гидродинамического возмущения; гидрофоны; помехоустойчивость; волны давления; тарировка; piezoelectric sensor; pulse pressure; electrical characteristics; high-voltage discharge; closed volume of liquid